Telediagnosis of Transbronchial Fine Needle Aspirations – A Feasibility Study - K. Kayser; G. Kayser; H. D. Becker; F. Herth (Analytical Cellular Pathology)
Aim: To analyze the diagnostic accuracy of telediagnostic procedures for transbronchial fine needle aspirations. Material and Methods: A double blind study was performed on cytological slides of 54 randomly selected cases with transbronchial fine needle aspirations. The slides were digitized using a Leica digital camera DC100 mounted on a microscope Leica Laborlux S, and analyzed by an experienced pathologist without knowing the definite diagnosis or any additional clinical data. The diagnoses stated by analyzing the digital images were compared to the final conventional diagnoses. In addition, the duration of the digital diagnosis, used magnifications, and difficulties for correct sampling were documented. Results: The “digital” diagnoses of the 54 cases were all in general agreement with the definite diagnoses. No wrong positive or wrong negative case in respect to malignant/non‐malignant (31/23) or to small cell/non‐small cell (9/22) occurred. The performance of a digital diagnosis lasted for 115 s at average (15–260 s), and is significantly longer compared to that of conventional fine needle aspiration judgement (20 s). The screening magnification was commonly set to ×2.5, that for definite diagnostic analysis ×40. Benign diseases (2 tuberculosis and 3 sarcoidosis cases) were correctly classified. Conclusions: Telepathology systems can probably be used for fine needle aspiration analysis without major diagnostic errors. Their use can improve the endoscopic sampling and avoid second anesthesia when missing the lesion of request during the first examination.